2021
DOI: 10.3389/fmats.2021.654841
|View full text |Cite
|
Sign up to set email alerts
|

Biomass-Derived Carbonaceous Materials to Achieve High-Energy-Density Supercapacitors

Abstract: Biomass-derived carbonaceous materials are considered as one of the most perspective electrodes for symmetric supercapacitors working with alkaline-basic electrolytes. However, they still exhibit lower energy density. Herein, we demonstrate the capacitance performance of the commercial carbon product (YP-50F, “Kuraray Europe” GmbH), obtained from coconuts, in symmetric supercapacitors by using lithium and sodium organic electrolytes. It is found that YP-50F delivers higher energy density when lithium electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The carbon surface functionality was further characterized by XPS (Table and Figure S2), determining the elemental composition on the outermost surface layers of the carbon particles (i.e., up to 5 nm depth). Analysis of the C 1s region indicates that there are five types of carbon functionalities present in the YP-50F carbon film, namely, the hydrocarbons ( C– C/ C– H groups at 284.9 eV), phenols or ethers ( C –OH/ C –O–C at 285.9 eV), carbonyls ( C O at 287.3 eV), carboxylic acids or esters (O– C O at 289.5 eV), and PTFE binder ( C– F at 291.2 eV). ,, The O 1s XPS spectrum is consistent with the analysis of the C 1s XPS spectrum, with three peaks being observed that are assigned to carbonyl groups ( O C at 531.5 eV), phenols or esters (C– O H/C– O– C at 532.5 eV), and carboxylic groups ( O C–OH at 533.5 eV). ,, A percentage of oxygen-containing groups on the carbon surfaces of 5.2% (by mole) is obtained by determining their contribution to the total area under the C 1s curve after subtracting the binder contribution (C–F peak) (Table ). This value agrees well with the oxygen content of 4.4% for YP-50F in the literature, i.e., a C:O ratio of 1:18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon surface functionality was further characterized by XPS (Table and Figure S2), determining the elemental composition on the outermost surface layers of the carbon particles (i.e., up to 5 nm depth). Analysis of the C 1s region indicates that there are five types of carbon functionalities present in the YP-50F carbon film, namely, the hydrocarbons ( C– C/ C– H groups at 284.9 eV), phenols or ethers ( C –OH/ C –O–C at 285.9 eV), carbonyls ( C O at 287.3 eV), carboxylic acids or esters (O– C O at 289.5 eV), and PTFE binder ( C– F at 291.2 eV). ,, The O 1s XPS spectrum is consistent with the analysis of the C 1s XPS spectrum, with three peaks being observed that are assigned to carbonyl groups ( O C at 531.5 eV), phenols or esters (C– O H/C– O– C at 532.5 eV), and carboxylic groups ( O C–OH at 533.5 eV). ,, A percentage of oxygen-containing groups on the carbon surfaces of 5.2% (by mole) is obtained by determining their contribution to the total area under the C 1s curve after subtracting the binder contribution (C–F peak) (Table ). This value agrees well with the oxygen content of 4.4% for YP-50F in the literature, i.e., a C:O ratio of 1:18 .…”
Section: Resultsmentioning
confidence: 99%
“…26,33,34 The O 1s XPS spectrum is consistent with the analysis of the C 1s XPS spectrum, with three peaks being observed that are assigned to carbonyl groups (O�C at 531.5 eV), phenols or esters (C−OH/C− O−C at 532.5 eV), and carboxylic groups (O�C−OH at 533.5 eV). 26,33,34 A percentage of oxygen-containing groups on the carbon surfaces of 5.2% (by mole) is obtained by determining their contribution to the total area under the C 1s curve after subtracting the binder contribution (C−F peak) (Table 1). This value agrees well with the oxygen content of 4.4% for YP-50F in the literature, i.e., a C:O ratio of 1:18.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a result, cost-effective devices that are made up of carbon sources that are renewable and workable are needed (Vijayakumar et al, 2018). Recent breakthroughs in the use of biomass-derived carbon materials in supercapacitors had shown the simplicity in boosting the energy density of produced electrodes using various electrolytic processes (Karamanova et al, 2021). Supercapacitors, fuel cells and lithium batteries have all been shown…”
Section: Energy Storagementioning
confidence: 99%
“…Most commercial supercapacitors are currently characterized by high carbonaceous materials. , Nevertheless, these supercapacitors may not deliver desirable ED, PD, or efficiencies, and their specific capacitance drops dramatically when exposed to a high current. As a result, great emphasis was placed on boosting the specific capacitance of supercapacitors and the efficiency of high current densities via the development of nano-heterostructured materials with higher surface areas . In this context, transition metal oxides (TMOs) and their nanocomposite are considered the most effective and attractive electrode materials in the supercapacitor .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, great emphasis was placed on boosting the specific capacitance of supercapacitors and the efficiency of high current densities via the development of nanoheterostructured materials with higher surface areas. 10 In this context, transition metal oxides (TMOs) and their nanocomposite are considered the most effective and attractive electrode materials in the supercapacitor. 11 make numerous nanostructures, providing a bigger theoretical capacitance, and having a large surface area.…”
Section: Introductionmentioning
confidence: 99%